Detection of Porcine and Bovine Gelatine in Dental Materials - Lestari, Widya; Irfan, Nining I.; Mirghani, Mohamed Elwathig Saeed; Octavianti, Fitri (2021)
This poster was submitted to Research Poster Competition with the theme" Educating Society Via Halal Knowledge 2019". Organised by Social Advancement and Happiness Research Ouster and Universiti Malaya Research Centre. Held on 14th November 2019 at Universiti Malaya.